APPLICATION OF THE BEHAVIORALLY ANCHORED RATING SCALE (BARS) IN ASSESSING EMPLOYEES’ OCCUPATIONAL SAFETY AND HEALTH SITUATIONAL AWARENESS - Ahmad Padhil; Dirgahayu Lantara; Lutfiah Putri; Andi Pawennari (Journal of Vocational Health Studies, 2025)
Background: In 2017, at PT. XY, the average Frequency Rate (FR) was 4.68 accidents for every one million working hours, while the average Severity Rate (SR) was 336.16 lost workdays per one million work hours. These indicators reveal that 264 accidents and 18.983 working days lost during 56.469.736 working hours throughout the current year. Purpose: This research aims to determine the level of alertness among workers and investigate their behavior in carrying out tasks at the PT. XY factory. Method: Worker data were collected using sampling techniques and analyzed employing the Behaviorally Anchored Rating Scale (BARS) method to provide potential dangers and worker behavior in the PT. XY factory section. The research approach applied was quantitative, collecting data through the distribution of 44 questionnaires to workers in that section. Result: The potential hazards occurring in the PT. XY factory were attributed to workers’ lack of attention to Situational Awareness (SA) while doing work, where in the PT. XY factory section there are three processes, namely first press, second press, and filtration stage. The results of the confidence levels in the office section of the PT. XY factory showed actual accuracy and perceived accuracy values of 46.67% and 86.67%, respectively. In the process section, workers exhibited actual accuracy and perceived accuracy values of 42.85% and 84.28%, while in the maintenance section, the actual accuracy value was 44.81% and the perceived accuracy was 84.90%. Conclusion: Based on data analysis, office workers showed the highest level of alertness (65.00%), followed by maintenance workers (63.67%), while workers in the process section showed the lowest alertness level (63.00%).